GAGASAN PENGATURAN AUDITOR HUKUM DI DALAM UNDANG-UNDANG SEBAGAI UPAYA MENINGKATKAN RULE OF LAW INDEX INDONESIA - Anand, Ghansham; Nugraha, Xavier; Wibisono, Berardus Bilyarto (Badan Pembinaan Hukum Nasional, 2024)
In Indonesia, there are legal auditors whose job is to conduct legal audits, so that they can improve Indonesia's RoL indicators, considering that one of the indicators is Regulatory Enforcement. However, it turns out that there is a legal vacuum (leemten in het recht) related to this legal auditor in Indonesia, so it is necessary to regulate this legal auditor in the law to fill the legal vacuum. The formulation of the problem in this article: First, what is the urgency of regulating legal auditors in law? Second, how is the formulation of legal auditor arrangements in statutory regulations? This legal research is a legal research with a statutory and conceptual approach. The legal data of this research is secondary data with primary and secondary legal materials. The results of this research. As for the results of this study, first, the urgency of regulating legal auditors in law, there are at least 4 (four): 1) Improving the Rule of Law Index (RoI) in Indonesia; 2) The realization of the function of law as a tool of social control (law as a tool of social engineering); 3) Provide standardized standards and criteria for auditors; and 4) Provide legal protection and realize legal certainty for business actors. Related to the formulation of legal auditor arrangements in this law is qualified into 2 (two), namely in terms of material and formal.